Energy conservation strategies in named data networking based MANET using congestion control: A review - Farkhana, Muchtar; Abdul Hanan, Abdullah; Al-Adhaileh, Mosleh; Kamal Z., Zamli (Elsevier, 2020)
Research in Named Data Networking-based Mobile Ad-hoc Network (NDN based MANET) has experienced a lot of momentum and development in recent years. Such robust developments in the specific area surely contributes to advanced possibilities that Named Data Networking (NDN) can provide compared to traditional host centric networking (HCN) solutions such as TCP/IP for dynamic routing that is much needed for MANET environment. However, our observation indicates that issues pertaining to the association of network congestion and energy wastage in NDN based MANET has never been explored by any previous researcher. In fact, discussions as to how congestion control was implemented in NDN based MANET is also scarce and no research to date has yet come forward to suggest a complete congestion control solution for NDN based MANET. Therefore, this article reviews the congestion control solution done by previous researcher for NDN in general to understand the characteristic of congestion control solution should be for NDN based MANET. In addition to these reviews, we propose several criteria on congestion control solution that should be incorporated in the NDN based MANET environment.